2007
DOI: 10.1021/jp075693l
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Solvation Dynamics in a Neat Ionic Liquid and Ionic Liquid Microemulsion:  Excitation Wavelength Dependence

Abstract: Solvation dynamics in a neat ionic liquid, 1-pentyl-3-methyl-imidazolium tetra-flouroborate ([pmim][BF4]) and its microemulsion in Triton X-100 (TX-100)/benzene is studied using femtosecond up-conversion. In both the neat ionic liquid and the microemulsion, the solvation dynamics is found to depend on excitation wavelength (lambda(ex)). The lambda(ex) dependence is attributed to structural heterogeneity in neat ionic liquid (IL) and in IL microemulsion. In neat IL, the heterogeneity arises from clustering of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 87 publications
7
123
2
Order By: Relevance
“…36 (There is a growing body of work on the subject of ionic liquids in micelles, microemulsions, and related systems. [37][38][39][40][41][42][43] ) Because coumarin 153 is only sparingly soluble and weakly fluorescent in water, a clear distinction can be made between its fluorescent properties in the bulk ionic liquid and those in the micelles formed from the ionic liquid. We concluded from this study that the same entity is responsible for the majority of the solvation in both the bulk and micellar [CVIM + ][Br -] ionic liquid, namely, as we have suggested elsewhere, [23][24][25] that it is the imidazolium cation.…”
Section: Introductionmentioning
confidence: 99%
“…36 (There is a growing body of work on the subject of ionic liquids in micelles, microemulsions, and related systems. [37][38][39][40][41][42][43] ) Because coumarin 153 is only sparingly soluble and weakly fluorescent in water, a clear distinction can be made between its fluorescent properties in the bulk ionic liquid and those in the micelles formed from the ionic liquid. We concluded from this study that the same entity is responsible for the majority of the solvation in both the bulk and micellar [CVIM + ][Br -] ionic liquid, namely, as we have suggested elsewhere, [23][24][25] that it is the imidazolium cation.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, bicontinuous structures could not be identified for [bmim] [BF 4 ]/TX-100/cyclohexane systems since phase separation occurred at higher cyclohexane weight fractions. (Adhikari et al, 2007;Adhikari et al, 2009). Surprisingly, the ternary phase diagram has not yet been documented in literature.…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 97%
“…A so-called red edge exication shift (REEs) denotes the shift in the wavelength of maximum fluorescence emission towards higher wavelengths, caused by a shift in the excitation wavelength towards the red edge of the absorption band (Demchenko 1982;Mukherjee & Chattopadhyay 2005). For the RTIL microemulsion faster solvation dynamics and a slower anisotropy decay with increasing λ ex has been reported (Adhikari et al, 2007). The authors explained these observations by a higher viscosity and polarity of the core of the reverse microemulsion compared to that at the interface.…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 99%
“…More detailed information was gained through FTIR (Gao et al, 2006b), 1 H NMR (Gao et al, 2006b;Gao et al, 2008b), UV-vis spectroscopy (Gao et al, 2006b;Gao et al, 2008b;Gao et al, 2005b;Li et al, 2007b) and conductivity measurements (Gao et al, 2006b;Gao et al, 2008b;Li et al, 2005a). Sarkar and his coworkers (Adhikari et al, 2007;Chakrabarty et al, 2005;Seth et al, 2006Seth et al, , 2007aSeth et al, 2007b) initiated the work of applying steady-state and time-resolved fluorescence spectroscopy to investigate IL based microemulsions. Coumarin 151, 153 and 490 were adopted as the probes.…”
Section: Ionic Liquid Based Microemulsionsmentioning
confidence: 99%
“…As the length of the alkyl chain increases, the nonpolar domains become larger and more connected, and cause swelling of the ionic network, in a manner analogous to microphase separation (Lopes & Padua, 2006). Recently, the results of X-ray diffraction (XRD) experiment (Triolo et al, 2007), fluorescent spectra (Hu & Margulis, 2006), Raman spectra (Iwata et al, 2007;Shigeto & Hamaguchi, 2006), NMR (Mele et al, 2006), femtosecond solvation dynamics study (Adhikari et al, 2007) and optical Kerr Effect spectra (Xiao et al, 2007) of 1-alkyl-3-methylimidazolium ILs also suggested the presence of heterogeneous structures. Furthermore, the result of the XRD experiment also reflected that the size of the inhomogeneous structures is proportional to the length of the alkyl chain (Triolo et al, 2007).…”
Section: Supramolecular Structures In Liquid Phasementioning
confidence: 99%